Population, Reproductive and Fishery Dynamics of Spotted Box Crab (Calappa philargius), a New Claw-Only Fishery Species, in the Southern Taiwan Strait, China - Lin, Bai-an; Jiang, Yan; Boenish, Robert; Xu, Qing; Liu, Min (Frontiers in Marine Science, 2021)
The spotted box crab Calappa philargius (Calappidae) is an increasingly consumed species in China, mainly sourced from a claw-only fishery. This species has not been well-characterized in the literature, thus study is warranted to inform sustainable management approaches. Here we report on the first in-depth overview on biology and fishery dynamics of C. philargius in the southern Taiwan Strait of China. Whole body crabs (N = 1009) were collected monthly from January to December 2019 from trawlers, operating in the southern Taiwan Strait; sample collection was absent from MayJuly because of the national fishing moratorium regulation. Sex ratio, growth pattern, size at maturity and fecundity were estimated. The overall male: female ratio was 1: 1.47, significantly differing from the 1: 1 (p < 0.01); monthly sex ratio variations were also significant (p < 0.01), suggesting possible seasonal sexual segregation. We found the carapace widths (CW) of males were significantly larger than those of females (p < 0.01). Based on percentages of mature females (carrying eggs on abdominal pleopods), we identified twin spawning events, JanuaryApril and AugustOctober with the overall peaks occurring in February and April. Size at 50% female maturity was 11.47 cm CW. Female absolute fecundity was significantly related to CW via a power function relationship (N = 14, p < 0.01). The estimated average claw yield was 36.28  3.07% of the whole body weight (N = 95), irrespective of sex and size (p > 0.5). Capture and trade data of C. philargius using trawl and trap fishing gears were documented to characterize claw-only fishery dynamics for future research and sustainable use.